1985
DOI: 10.1111/j.1365-2133.1985.tb02403.x
|View full text |Cite
|
Sign up to set email alerts
|

Significance of non-lymphoid ('accessory') cells in malignant lymphomas and pseudolymphomas of the skin

Abstract: We investigated the co-distribution of lymphocyte subpopulations and non-lymphoid 'accessory' cells in 35 cases of cutaneous lymphoproliferative diseases (T-cell lymphoma, 10 cases; B-cell lymphoma, 17 cases; pseudolymphoma, 8 cases) using immunohistochemical methods. T-zone histiocytes and particularly Langerhans cells were abundant in all cutaneous T-cell lymphomas, but were also found in B-cell lymphomas. T-zone histiocytes were associated with T-lymphocytes, especially T-helper cells, but not with T-suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…A follicular B cell pattern with polyclonal light chains proves the diagnosis of a pseudolymphoma. A similar pattern may be observed in centroblastic-centrocytic lymphoma (45), but will usually be associated with monoclonal light chains. In case of polyclonality, reactive germinal centers within a malignant lesion, however, will have to be excluded by careful observation of tbe overall pattern and tbe cytologic features.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…A follicular B cell pattern with polyclonal light chains proves the diagnosis of a pseudolymphoma. A similar pattern may be observed in centroblastic-centrocytic lymphoma (45), but will usually be associated with monoclonal light chains. In case of polyclonality, reactive germinal centers within a malignant lesion, however, will have to be excluded by careful observation of tbe overall pattern and tbe cytologic features.…”
Section: Discussionsupporting
confidence: 62%
“…Tbe non follicular B cell pattern bas to be diflerentiated from specific infiltrates in cbronic lymphocytic leukemia. The expression of CD 5 on the B cells of the latter disease will help to distinguish both entities (45). The nodular T cell pattern, which usually reveals small nodular dermal infiltrates, can be separated from cutaneous T cell lympboma by histological features and the low proliferation rate (47).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in T-cell infiltrates, they noted different DC distributions in malignant and inflammatory infiltrates, with larger, more loosely arranged DC aggregates seen in malignant lesions. Smolle J et al [14] investigated the distribution of non-lymphoid accessory cells in 35 lymphoproliferative disease specimens using Fig. 4 Immunolabeling of anti FXIIIa.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages in cutaneous infiltrates have not been extensively studied. Only one study showed that macrophages are more numerous in CLH than in B-or T-cell lymphoma [14].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation